Physicians’ and Users’ Perceptions towards Wearable Health Devices - Narassima M Seshadri; Anbuudayasankar S P; Shriram Kris Vasudevan; Abhinavaram J (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Healthcare plays a vital role in economic development of a country, and has a major impact on the entire wellness of humankind. One of the biggest issues of all times, Blood Pressure is prevailing in patients of all countries.  In developing countries like India, it is prevalent among people of diverse age groups, which somehow permeates into their wellness, reflecting and slowing down the growth of the country as well as that of an individual. As Blood Pressure is identified as one of the major contributors to Cardio Vascular Diseases, there is an urge to educate people about the consequences. The research focuses on various factors and their levels of impact on acceptance of Mobile Health Management Services. Appropriate tests have been carried out for validating this hypothesis. All the details are presented in the results’ section with clear discussion and description.